Efeito de um programa de reabilitação de baixo custo, baseado em teste funcional, com e sem supervisão do fisioterapeuta na DPOC: ensaio clínico controlado e randomizado - Silva, Marcela Maria Carvalho da (2021)
Introduction: Patients with COPD present a decline in lung function, tolerance to physical exercise and quality of life, and the pulmonary rehabilitation program (PRP) is essential for the prevention and improvement of this clinical condition. However, access to PRP in patients with COPD is restricted, limiting it to 10% of this population, therefore, alternative models that expand accessibility need to be tested. The literature is still conflicting on the subject, leaving gaps on how to develop the individualized and progressive prescription from functional tests, considering the low cost, and also on what is the degree of supervision of the ideal physiotherapist to obtain positive results. From the gaps in the literature, this thesis was composed of two studies. Study 1- study STUDY I: Objective: To describe an accessible, low-cost and individualized pulmonary rehabilitation protocol based on functional clinical tests for individuals with symptomatic COPD. Methods: This is a descriptive study, referring to a low cost pulmonary rehabilitation protocol, according to different degrees of supervision by the physiotherapist, being registered in the Brazilian Clinical Trials Registry (ReBec) URL: http://www.ensaiosclinicos.gov.br/rg/RBR-533hht/ number UTN code U1111-1220-8245. Results: The protocol was designed according to the basic principles of PR prescription, lasting eight weeks, however, low cost tools were used for the prescription and progression of aerobic training intensity, based on the individual performance of the functional tests (six-minute step test (TD6), six-minute walk test (6MWT) and one-minute sit and stand test (TSL1) and upper limb strength training (test of ten maximum repetitions with free weights). In addition, two levels of supervision by the physiotherapist were tested, as one group had face-to-face guidance from the physiotherapist weekly, during the eight weeks, and each week there was a weekly meeting at the specialized center and other days held at home, and another group received a single orientation in the first week of the PR (but also had an individualized prescription). Conclusion: An affordable and low-cost PRP was proposed based on individualized functional tests and it is expected that the PRP prescription proposed in this protocol will have positive effects on exercise tolerance and quality of life, promoting accessibility to treatment in patients with COPD.STUDY II: Objectives: to describe and verify the effect on exercise tolerance, dyspnea sensation and health-related quality of life of a low-cost PRP based on functional tests, performed at home, with or without supervision by the weekly physical therapist. Methods: This is a clinical trial, randomized and controlled, performed at the Laboratory of Respiratory Physiotherapy and Spirometry at the Federal University of São Carlos. According to the established inclusion and exclusion criteria, 272 volunteers were contacted, of whom 89 patients were evaluated, through anamnesis, laboratory blood tests, physical examination and spirometry. All patients were assessed by functional tests (6-minute walk test, 6-minute step test and 1-minute sit and stand test), dyspnea scale, exercise tolerance and pre-and post-intervention health-related quality of life. Of the total number of patients evaluated, 50 were included in the rehabilitation and, randomized into two groups, 25 patients in the orientation group (OG) who participated in a single meeting for orientation (educational) and 25 patients in the supervised exercise group (SG) with weekly meetings with the physiotherapist. Results: There was no difference between groups at baseline. Time influence (pre and post intervention) was found with a statistically significant difference (p<0.01) for functional tests, sensation of dyspnea and quality of life. Regarding the 6-minute step test, 6-minute walk test, mMRC and CAT, a significant difference was also observed between the groups, verified in the interaction (p<0.01) and confirmed by the syntax analysis (p<0.01) (CAT: SG= of 19, 5±6.8 to 13±7.8 points, OG= from 17±7.6 to 15±10 points), (mMRC: SG= from 2[2-3] to 1[1-2], OG= from 2[2-3] to 2[1-3] points) and (Distance walked 6-minute walk test: SG: from 367.7 ± 84m to 433.2±88.8m, OG= from 396.2 ± 97.2m to 418, 33±83.8m) and 6-step test (SG= from 67.1 ± 25.7 to 93.5 ± 37.2, OG= from 69.6 ± 19.5 to 82.3 ± 25.2 numbers of steps).). In conclusion, the results showed that the low-cost PRP had a positive effect on exercise tolerance, dyspnea and health-related quality of life, which was greater in the presence of face-to-face weekly supervision by the physical therapist, when compared to non-supervision.